Technical Modernization and Land Tillage Technologies in Agriculture - Asadullayevich, Abdullayev Dilmurod; Yusupovich, Mahmudov Rafiqjon (American Journal of Botany and Bioengineering, 2026)
Guaranteed provision of the country's population with quality food products and seamless integration of industrial sectors with raw materials are strategic priorities of the agrarian policy. The fundamental reforms being implemented in Uzbekistan's agriculture have raised the efficiency of the sector to a qualitatively new level by enlarging farms, modernizing the material and technical base, and improving the service delivery system. The results achieved in cotton and grain growing, which are considered the locomotive sectors of agriculture, in particular, the country's success in ensuring not only grain independence, but also in forming export potential, are a vivid reflection of systemic changes in the sector. In the context of global climate change, ensuring the stability of the agricultural sector, increasing the competitiveness of the sector, and widely introducing advanced resource-saving technologies into practice are of utmost importance. This study analyzes mechanisms for increasing regional efficiency by integrating innovative approaches, digital technologies, and advanced international practices into agricultural processes.